ENHANCING TOLERANCE THROUGH CROSS-CULTURAL EDUCATION IN A NON-METROPOLITAN ISLAMIC UNIVERSITY - Ardian Dewangga; Elok Nimasari; Ana Maghfiroh; Khozaeni Bin Rahmad (SOSIOEDUKASI, 2026)
This study addresses the issue of student tolerance within Islamic universities in Indonesia, highlighting the gap between the theological ideal of rahmatan lil ‘alamin and the practical challenges of campus diversity. The research aims to explore how cross-cultural educational experiences—through courses, community service, and student exchange programs—shape students’ attitudes toward tolerance. Using a qualitative approach, data were collected through in-depth interviews with four students, both participants and non-participants of cross-cultural programs. The data were analyzed using reflexive thematic analysis. The findings reveal that students with intercultural experiences demonstrated greater empathy, reflection, and practical tolerance, while those without such exposure tended to conceptualize tolerance more abstractly. Integration of Islamic values, particularly rahmatan lil ‘alamin, provided a strong ethical foundation, although institutional limitations restricted equal access to such opportunities.Cross-cultural education, when aligned with Islamic principles, fosters tolerance as both a theological commitment and lived practice. This underscores the importance of embedding intercultural learning into the curriculum of Islamic higher education to prepare students as responsible global citizens.